The Cambridge Handbook of Health Research Regulation - Laurie, Graeme; Dove, Edward; Ganguli-Mitra, Agomoni; McMillan, Catriona; Postan, Emily; Sethi, Nayha; Sorbie, Annie (Social Sciences, 2021)
This multi-disciplinary Handbook examines human health research and its regulation. It uses real world examples - research using patient data, tissue and other human materials - to explore current challenges in delivering good medical research for the public good. Practical recommendations for real-world situations are a key feature of the book.